Effectiveness of self-directed learning strategy in Dentistry - Buenaventura, Criszel F.; Sana, Erlyn A., PhD (2018)
The evolution of curriculum in the health sciences is accompanied with promotion of various teaching-learning (TL) strategies to enhance learning experience of students. However, despite the fact that several TL strategies are now available, many dental colleges and universities in the Philippines still primarily utilize lecture. One of the strategies being promoted in dentistry is self-directed learning (SDL). It is believed to be beneficial in dentistry because the students are adult learners and several studies claim that an individualized instruction such as SDL is effective in adult learning. SDL may also prove to be valuable because students who undergo SDL display better academic performance than the ones taught with traditional strategy (Al-Nasseri, 2014; Pai et al, 2014). This study determined the effectiveness of SDL by comparing it with lecture using the students‟ perceptions of their learning experience and their cognitive performance. It was conducted at a private School of Dentistry in Manila across the four year levels of dentistry proper. Total enumeration was done in the selection of student-respondents who were exposed to both SDL and lecture. After each learning experience, two kinds of data were collected ? post- test scores that indicate the students‟ cognitive performance and Assessment of University Teaching Activities Questionnaire (AUTAQ) results indicating students‟ perceptions on their learning experience. Results showed that in terms of students‟ perceptions, SDL is a more effective TL method than lecture. However, in terms of cognitive performance, ivlecture was more effective among the first year students. Among the higher year levels, SDL and lecture were equally effective. The differences in students‟ perceptions and cognitive performance across the four year levels were also determined. Results showed that the students‟ perceptions did not vary across the four year levels but the lower year levels exhibited higher cognitive performance after lecture while the higher year levels displayed higher cognitive performance after SDL. Correlations between the students‟ scores in post-tests and their perception of learning experience showed that there is no correlation between these two factors. It is concluded that SDL is as equally effective as lectures but it must be used cautiously in lower year levels where lecture is still more beneficial. Further studies comparing SDL and other TL strategies with a more comprehensive review of literature are recommended.
also available in pdf
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Ma. Elizabeth M. Grageda PTRP MHPEd, Reader/Critic; Melflor A. Atienza MD, MHPEd, Member; Maria Lourdes Dorothy S. Salvacion DMD MHPEd, Member; Nomar Alviar MD, MHPEd, Member.
Keywords: Self-directed learning; Dentistry; SDL vs Lecture